Penerapan Metode Pembelajaran Berbasis Masalah Pada Pokok Bahasan Lingkaran Di Kelas Viii Smp Negeri 1 Polewali - Fatimah Fatimah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2012)
This research was designed under experimental research and conducted in SMP Negeri 1 Polewali with class VIII as the population. Class VIII2 was selected as experiment class and class VIII3 as control class. The sample selected randomly assuming that students’ ability in both classes tend to be homogeneous. In this research, both classes were given a different treatment, Problem Basic Learning Model applied in experimental class while the control class did not apply it with the same teaching material; that is circle. Based on statistical descriptive analysis result obtained that in experimental class with Problem Basic Learning Model, students’ average score was 71,7 with standard deviation 10,09, 31 students or 86,12 % were in complete category and 5 students or 13, 88% were in incomplete category. Whereas students’ average score in control class without Problem Basic Learning Model was 63,9 with standard deviation 8, 67 and 23 students or 63,89 % were in complete category and 13 students or 36,11% were in incomplete category. Based on inferential statistical analysis obtained that there was a significant difference in students learning outcomes on the class applied Problem Basic Learning Model and the students who taught without applying Problem Basic Learning Model.